Три долі Івана Шовкопляса - Кулаковська, Л.В. (Кам’яна доба України, 2011)
Стаття присвячена науковій діяльності Івана Шовкопляс. Автор виділив три основні вектори своєї наукової діяльності: дослідження палеоліту, музей будівництва та навчання. The article dedicated to scientific activity of Ivan Shovkoplyas. Author emphasised three main vectors of his scientific career: investigation of Paleolithic sites, museum construction and teaching.